Vitamin D and cancer-related fatigue in elderly patients: mechanisms and therapeutic insights—a narrative review - Wu, Juan; Chi, Jinzheng; Zhang, Yu (Frontiers in Nutrition, 2025)
Cancer-related fatigue (CRF) is a prevalent and debilitating symptom in elderly cancer patients. According to the National Comprehensive Cancer Network (NCCN) and international consensus, CRF is defined as a persistent, multidimensional fatigue disproportionate to activity, unrelieved by rest, and involving physical, emotional, and cognitive domains. Diagnosis requires standardized patient-reported scales, objective biomarkers (e.g., inflammatory and metabolic indices), and exclusion of comorbidities such as anemia or organ dysfunction. In elderly patients, CRF arises from interrelated alterations, including chronic inflammation, neuroendocrine dysregulation, circadian disruption, and progressive muscle atrophy, that perpetuate a vicious cycle. Current treatments encompass pharmacological agents (e.g., corticosteroids, psychostimulants, antidepressants, and traditional Chinese medicine, primarily studied in China) and non-pharmacological modalities (e.g., exercise, acupuncture, and cognitive-behavioral therapy), yet efficacy remains inconsistent. Emerging approaches such as mitochondrial modulators and bright light therapy are expanding the therapeutic landscape. Vitamin D, particularly cholecalciferol (vitamin D3), is commonly deficient in older adults and shows promise in alleviating CRF through anti-inflammatory, immunomodulatory, neuroprotective, and myogenic effects. This narrative review summarizes current evidence on vitamin D3’s mechanisms and clinical value, highlights its role as a multi-target modulator, and explores its integration into personalized CRF management. Future studies should refine dosing strategies, clarify responses in the elderly, and assess the synergy between conventional and novel interventions.